Computed tomography imaging strategies and perspectives in orbital fractures (Journal of Applied Oral Science, 2007)
OBJECTIVE: The objective of this study was to demonstrate the sensitivity and specificity of multislice computed tomography (CT) for diagnosis of orbital fractures following different protocols, using an independent workstation. MATERIALS AND METHODS: CT images of 36 patients with maxillofacial fractures (symptomatic to orbit region) who were submitted to multislice CT scanning were analyzed, retrospectively. The images were interpreted based on 5 protocols, using an independent workstation: 1) axial (original images); 2) multiplanar reconstruction (MPR); 3) 3D images; 4) association of axial/MPR/3D images and 5) coronal images. The evaluated anatomical sites were divided according to the orbital walls: lateral (with or without zygomatic frontal process fracture); medial; superior (roof) and inferior (anterior, medial). The collected data were analyzed statistically using a validity test (Youden's J index; p